Waste palm shell converted to high efficient activated carbon by chemical activation method and its adsorption capacity tested by water filtration - Rahman, Md. Mokhlesur; Awang, Mohamed; Mohosina, B. S.; Yunus, Kamaruzzaman; Wan Nik, W.B.; Che Adnan, C. M. (Elsevier, 2012)
The concentrations of phosphoric acid on the characteristics of high efficient activated carbon were investigated. Adsorptions capacities of activated carbon prepared by chemical method were carried out to evaluate the adsorptive of some heavy metals. It was found that treated (palm shell by sulphuric acid, 5%) raw material reduces contain of impurities and increases Brunet Elmer Teller (BET) surface area of the prepared activated carbon. The most advantageous BET surface area was obtained with following conditions; phosphoric acid concentration was 30%, treated raw material and 5000C was activation temperature with holding time of 2 hours. Obtained BET surface area is 1058 m2g-1 and the average pore diameter was found 20.64 nm. Scanning electron microscopy (SEM) also confirmed the pore size distribution on the activated carbon. The maximum thermal stability was observed up to 6000C by thermal gravimetric analyzer (TGA). Adsorption capacity of the activated carbon was tested passed by artificially polluted water through a water filtering column and it was observed 100% of Cr was adsorbed followed by Pb (99.8 %), Cd (99.5 %) and Cu (25 %).